2011
DOI: 10.1051/0004-6361/201015247
|View full text |Cite
|
Sign up to set email alerts
|

Megamaser detection and nuclear obscuration in Seyfert galaxies

Abstract: We revisit the relation between H 2 O maser detection rate and nuclear obscuration for a sample of 114 Seyfert galaxies, drawn from the CfA, 12µm and IRAS F25/F60 catalogs. These sources have mid-infrared spectra from the Spitzer Space Telescope and they are searched for X-ray and [O III] 5007Å fluxes from the literature. We use the strength of the [O IV] 25.9µm emission line as tracer for the intrinsic AGN strength. After normalization by [O IV] the observed X-ray flux provides information about X-ray absorpt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 117 publications
2
6
0
Order By: Relevance
“…This constrains the geometry of the maser source because the surface area for cooling should be optimised, favouring an elongated or flat structure (Lo 2005). The fact that mega-masers are almost exclusively found in Seyfert 2 galaxies (Ramolla et al 2011) is consistent with the picture that disc maser emission is produced and beamed close to the plane of the obscuring material. In NGC 1068, nuclear H 2 O A1, page 6 of 12 22 GHz maser emission is detected, spanning a velocity range of 600 km s −1 nearly symmetric about the systemic velocity of the galaxy (Greenhill & Gwinn 1997;Gallimore et al 2001).…”
Section: Cospatial Dust and Maser Discsupporting
confidence: 56%
“…This constrains the geometry of the maser source because the surface area for cooling should be optimised, favouring an elongated or flat structure (Lo 2005). The fact that mega-masers are almost exclusively found in Seyfert 2 galaxies (Ramolla et al 2011) is consistent with the picture that disc maser emission is produced and beamed close to the plane of the obscuring material. In NGC 1068, nuclear H 2 O A1, page 6 of 12 22 GHz maser emission is detected, spanning a velocity range of 600 km s −1 nearly symmetric about the systemic velocity of the galaxy (Greenhill & Gwinn 1997;Gallimore et al 2001).…”
Section: Cospatial Dust and Maser Discsupporting
confidence: 56%
“…For example, the most prolific class of AGN, the Sy 2 galaxies, have detection rates of up to ∼20%, while in "pure" Sy 1 galaxies the percentage of water maser detections never exceeds 1% (e.g. Braatz et al 2004;Bennert et al 2009;Zhang et al 2010;Ramolla et al 2011). …”
Section: The Water Maser Detection Rate In Nls1 Galaxiesmentioning
confidence: 99%
“…A number of studies have been also recently led with the goal of finding correlations between the occurrence of maser emission and host galaxies characteristics at several wavelengths. The main results of these studies are: the confirmation of the fact that H 2 O masers reside primarily in X-ray absorbed sources (Zhang et al 2010, Ramolla et al 2011, Zhu et al 2011, the larger radio luminosity found in H 2 O maser hosts w.r.t. that in non-maser galaxies (Zhang et al 2012), and the indication of the extinction-corrected [OIII]λ5007 flux as a good sample selection criterion to maximize the number of detections in maser searches (Zhu et al 2011; see also Zaw et al, these proceedings).…”
Section: Water Masers In Agn: Detection Rates and Host Galaxiesmentioning
confidence: 82%